Comprehensive Understanding of Closed Pores in Hard Carbon Anode for High-Energy Sodium-Ion Batteries - Gan, Siyang; Huang, Yujie; Hong, Ningyun; Zhang, Yinghao; Xiong, Bo; Zheng, Zhi; He, Zidong; Gao, Shengrui; Deng, Wentao; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo (Nano-Micro Letters, 2025)
Hard carbon (HC) is considered the most promising anode material for sodium-ion batteries (SIBs) due to its high cost-effectiveness and outstanding overall performance. However, the amorphous and intricate microstructure of HC poses significant challenges in elucidating the structure–performance relationship, which has led to persistent misinterpretations regarding the intrinsic characteristics of closed pores. An irrational construction methodology of closed pores inevitably results in diminished plateau capacity, which severely restricts the practical application of HC in high-energy-density scenarios. This review provides a systematic exposition of the conceptual framework and origination mechanisms of closed pores, offering critical insights into their structural characteristics and formation pathways. Subsequently, by correlating lattice parameters with defect configurations, the structure–performance relationships governing desolvation kinetics and sodium storage behavior are rigorously established. Furthermore, pioneering advancements in structural engineering are critically synthesized to establish fundamental design principles for the rational modulation of closed pores in HC. It is imperative to emphasize that adopting a molecular-level perspective, coupled with a synergistic kinetic/thermodynamic approach, is critical for understanding and controlling the transformation process from open pores to closed pores. These innovative perspectives are strategically designed to accelerate the commercialization of HC, thereby catalyzing the sustainable and high-efficiency development of SIBs. Highlights: 1 This review summarizes the latest advances in closed pore structures within hard carbon anodes for sodium-ion batteries, establishing a conceptual framework and origination mechanisms under a unified perspective of active sites. 2 The influence of closed pore characteristics on sodium storage behavior is systematically explored, with design principles proposed for directional regulation of pore structures. 3 Future research directions are highlighted, integrating advanced modification strategies with molecular-level design and dynamic/thermodynamic hybrid analyses for performance optimization.